Study of Sweep and Induced Dihedral Effects in Subsonic Axial Flow Compressor Passages—Part I: Design Considerations—Changes in Incidence, Deflection, and Streamline Curvature - P. V. Ramakrishna; M. Govardhan (International Journal of Rotating Machinery)
This article presents the study of Tip Chordline Sweeping (TCS) and Axial Sweeping (AXS) of low-speed axial compressor rotor blades against the performance of baseline unswept rotor (UNS) for different tip clearance levels. The first part of the paper discusses the changes in design parameters when the blades are swept, while the second part throws light on the effect of sweep on tip leakage flow-related phenomena. 15 domains are studied with 5 sweep configurations (0∘, 20∘ TCS, 30∘ TCS, 20∘ AXS, and 30∘ AXS) and for 3 tip clearances (0.0%, 0.7%, and 2.7% of the blade chord). A commercial CFD package is employed for the flow simulations and analysis. Results are well validated with experimental data. Forward sweep reduced the flow incidences. This is true all over the span with axial sweeping while little higher incidences below the mid span are observed with tip chordline sweeping. Sweeping is observed to lessen the flow turning. AXS rotors demonstrated more efficient energy transfer among the rotors. Tip chordline sweep deflected the flow towards the hub while effective positive dihedral induced with axial sweeping resulted in outward deflection of flow streamlines. These deflections are more at lower mass flow rates.